Training load and low back pain in German elite rowers - Winzem, M.; Voigt, H. F.; Hinrichs, T.; Platen, P. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Training load and biomechanical impact on the musculo skeletal system in elite rowing on international level are considerable. On the middle and long term, they can lead to severe chronic disorders of the musculoskeletal system, and especially of the lower back. The aim of this study was to evaluate training load as well as prevalence and characteristics of lower back pain in German elite rowers during the Olympic year 2008. Methods: 29 female rowers aged 22.2±3.1 (18-30) years and 38 male rowers aged 22.3±3.1 (18-32) years of the German national team have been interviewed about their mean training volume and training content. Furthermore,they have been asked about pain at the lower back (LBP) at the time of the interview and over the past 12 months (self-administered questionnaire). Indicated percentages refer to the number of athletes who answered the respective question. Results: The rowers began their career at the age of 12.2±1.9 (8-17) years. Elite rowers trained on average 22.8±5.3 (11-38) hours in 16.0±4.6 (8-32) training sessions per week. They spent 10.3 hours (46.3% of the whole training volume) with rowing on the water, 4.7 hours (21.7%) with weight training and 2.8 hours (12.3%) with rowing on an ergometer. The training distance on the water was 3961±1062 (1500-6000) km. 18 rowers (27.3%) stated to suffer from LBP at the time of the interview. Within the past 12 months, another 14 rowers (21.9%) had suffered from LBP. 25 of the 32 rowers with LBP (78.1%) stated to have pain during rowing, 23 (71.9%) subsequent to rowing, and 20 (62.5%) at rest, independent from rowing (multiple answers permitted). 21 rowers (65.6%) with LBP stated that they had consulted a physician for that reason with in the past 12 months. 12 rowers (37.5%) with LBP had to pause their training for that reason. The duration of the training break was 3.4±3.0 (0.5-10) weeks. According to the athlete`s individual estimation, the most frequent reason for LBP was "overuse" (24 rowers; 75%); while "acute injury" was only named by 4 rowers (12.5%) (multiple answers permitted). Conclusions: The high prevalence of LBP in German elite rowers supports the demand for adequate preventive and therapeutic measures. Technically exact chains of movement and motion patterns of rowing and rowing specific weight training have to be learned at an early age and have to be regularly monitored later on to prevent overuse of specifically stressed structures. The knowledge on pathophysiology of LBP is essential for the education of trainers at all stages and especially for trainers who engage in the formation of children and junior elite rowers.